Bear on the loose! - Lysiak, Hilde, 2006-; Lysiak, Matthew; Lew-Vriethoff, Joanne (2017)
When she hears reports of bear roaming the backyards of Selinsgrove, Hilde and her sister/photographer Izzy are determined to get the story for their own newspaper, the Orange Street News--but when they find out the culprit is a black bear cub, their scoop turns into a rescue mission
Appeals to 2nd-3rd graders
Reading level grade 2
Keywords: Lysiak, Hilde, -- 2006- -- Juvenile fiction; Reporters and reporting -- Juvenile fiction; Black bear -- Juvenile fiction; Wildlife rescue -- Juvenile fiction; Sisters -- Juvenile fiction; Children$1 (Bs bookss; Fiction; Detective and mystery fiction; Detective and mystery fiction; Fiction; Juvenile works